2021
DOI: 10.1021/acs.jpclett.1c02479
|View full text |Cite
|
Sign up to set email alerts
|

Time-Variable Chiroptical Vibrational Sum-Frequency Generation Spectroscopy of Chiral Chemical Solution

Abstract: Vibrational sum-frequency generation (VSFG) spectroscopy, a surface-specific technique, was shown to be useful even for characterizing the vibrational optical activity of chiral molecules in isotropic bulk liquids. However, accurately determining the spectroscopic parameters is still challenging because of the spectral congestion of chiroptical VSFG peaks with different amplitudes and phases. Here, we show that a time-variable infrared–visible chiroptical three-wave-mixing technique can be used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The signal loss in the present measurements can be attributed to the Gaussian shape of the ps probe pulse, which results in a gradual time-filtering of the fast RFID components. To mitigate this issue, the use of a time-asymmetric probe pulse with a sharp leading edge or the combination of other pulse shaping technologies ,, could lead to more effective suppression of the fast RFID components and thus further signal enhancement. We anticipate that this tr-CARS technique will be a valuable tool for determining the structures of organic molecules in condensed phase and for performing label-free vibrational imaging of C–H bond-rich organelles and biotoxic microplastics in biological specimens.…”
Section: Summary and A Few Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The signal loss in the present measurements can be attributed to the Gaussian shape of the ps probe pulse, which results in a gradual time-filtering of the fast RFID components. To mitigate this issue, the use of a time-asymmetric probe pulse with a sharp leading edge or the combination of other pulse shaping technologies ,, could lead to more effective suppression of the fast RFID components and thus further signal enhancement. We anticipate that this tr-CARS technique will be a valuable tool for determining the structures of organic molecules in condensed phase and for performing label-free vibrational imaging of C–H bond-rich organelles and biotoxic microplastics in biological specimens.…”
Section: Summary and A Few Concluding Remarksmentioning
confidence: 99%
“…Similar time-sampling approaches employing ps probe pulses have also been applied to vibrational sum-frequency-generation (VSFG) spectroscopy, a second-order nonlinear optical method, for the analysis of surface molecules or bulk enantiomers . Recent studies have demonstrated that time-resolved VSFG (tr-VSFG), using a time-asymmetric visible probe pulse, can be used to separate slower VSFG field components from faster ones in congested VSFG spectra, ,, resulting in improved spectral resolution. The global fitting of the tr-VSFG spectra with an appropriate theoretical model has been shown to be beneficial for obtaining more accurate and reliable spectroscopic parameters of the molecular system under investigation. ,, However, due to the selection rule of second-order nonlinear spectroscopy, this tr-VSFG technique is limited to the structural analysis of surface or bulk chiral molecules that lack centrosymmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 These authors integrated high-frequency polarization modulation into a specially constructed polarimeter, achieving performance on par with existing ROA instruments while reducing optomechanical complexity and polarization artifacts. Cho and coworkers 40 utilized vibrational sum-frequency generation, a variant of nonlinear-optical spectroscopy possessing interfacial (surface) specificity, to explore the possibility of realizing background-free chiroptical characterization with enhanced spectral resolution.…”
Section: ■ Novel Techniquesmentioning
confidence: 99%